Cable Guys - Lotz, Amanda D. (New York University Press, 2014)
The emergence of "male-centered serials" such as The Shield, Rescue Me, and Sons Of Anarchy and the challenges these characters face in negotiating modern masculinities. From the meth-dealing but devoted family man Walter White of AMC’s Breaking Bad, to the part-time basketball coach, part-time gigolo Ray Drecker of HBO’s Hung, depictions of male characters perplexed by societal expectations of men and anxious about changing American masculinity have become standard across the television landscape. Engaging with a wide variety of shows, including The League, Dexter, and Nip/Tuck, among many others, Amanda D. Lotz identifies the gradual incorporation of second-wave feminism into prevailing gender norms as the catalyst for the contested masculinities on display in contemporary cable dramas. Examining the emergence of “male-centered serials” such as The Shield, Rescue Me, and Sons of Anarchy and the challenges these characters face in negotiating modern masculinities, Lotz analyzes how these shows combine feminist approaches to fatherhood and marriage with more traditional constructions of masculine identity that emphasize men’s role as providers. She explores the dynamics of close male friendships both in groups, as in Entourage and Men of a Certain Age, wherein characters test the boundaries between the homosocial and homosexual in their relationships with each other, and in the dyadic intimacy depicted in Boston Legal and Scrubs. Cable Guys provides a much needed look into the under-considered subject of how constructions of masculinity continue to evolve on television.